Global DNA hypomethylation is associated with the development and poor prognosis of tongue squamous cell carcinoma. (2nd November 2015) - Chen, Hung‐Chih; Yang, Cheng‐Mei; Cheng, Jiin‐Tsuey; Tsai, Kuo‐Wang; Fu, Ting‐Ying; Liou, Huei‐Han; Tseng, Hui‐Hwa; Lee, Jang‐Hwa; Li, Guan‐Cheng; Wang, Jyh‐Seng; Hou, Yu‐Yi; Weng, Ta‐Jung; et al.
Abstract : Backgrounds: Oral cancer is the 4th leading cause of cancer death for males and the top cancer in young adult males in Taiwan. Tongue squamous cell carcinoma (TSCC) is a common oral cancer and generally associated with poor prognosis. Global DNA hypomethylation at the 5 position of cytosine (5mC) is a well‐known epigenetic feature of cancer. Therefore, the purpose of this study was to investigate the relationship of the global 5mC content with the tumorigenesis and prognosis of patients with TSCC. Methods: The levels of global 5mC were evaluated by immunohistochemistry using tissue microarray slides of 248 surgically resected TSCC and 202 corresponding tumor adjacent normal (TAN) tissues. Results: We found that the level of 5mC in TSCC ( P < 0.001) was significantly decreased as compared to TAN. Among TSCC tissues, decreased levels of 5mC were associated with female gender ( P = 0.036). In addition, the global hypomethylation was associated with the poor disease‐specific survival in TSCC patients (adjusted hazard ratio: 1.55, P = 0.043), especially for patients in older age group (> 50 years, P = 0.013), with moderate or poor cell differentiation ( P = 0.044), early stage of disease (I‐II, P = 0.046), small tumor size (T1–T2, P = 0.005), without lymph node involvement ( P = 0.041), and ever received postoperative radiotherapy ( P = 0.009). Conclusions: Global hypomethylation was an independent biomarker for the development and poor prognosis of TSCC.